Assessment of cognitive flexibility in personnel selection: Validity and acceptance of a gamified version of the Wisconsin Card Sorting Test - Björn E. Hommel; Regina Ruppel; Hannes Zacher (International Journal of Selection and Assessment, 2021)
The present study contributes to the emerging field of gamification in personnel selection by examining validity and acceptance of the Gamified Set-Shifting Task (GSST), which is based on a well-established neuropsychological test of cognitive flexibility, the Wisconsin Card Sorting Test (WCST). Results based on a sample of 180 participants in an online study provided preliminary support for construct and criterion-related validity. The GSST was better accepted among test-takers than both the WCST and a cognitive ability test. Overall, the findings suggest that the GSST may be an attractive and valid method to assist organizations in selecting employees who are able to adapt to changing environments.
Keywords: 650; cognitive ability; cognitive flexibility; gamification; personnel selection